Sensorimotor Oscillatory Phase–Power Interaction Gates Resting Human Corticospinal Output. (11th October 2018) - Hussain, Sara J; Claudino, Leonardo; Bönstrup, Marlene; Norato, Gina; Cruciani, Gabriel; Thompson, Ryan; Zrenner, Christoph; Ziemann, Ulf; Buch, Ethan; Cohen, Leonardo G
Abstract: Oscillatory activity within sensorimotor networks is characterized by time-varying changes in phase and power. The influence of interactions between sensorimotor oscillatory phase and power on human motor function, like corticospinal output, is unknown. We addressed this gap in knowledge by delivering transcranial magnetic stimulation (TMS) to the human motor cortex during electroencephalography recordings in 20 healthy participants. Motor evoked potentials, a measure of corticospinal excitability, were categorized offline based on the mu (8–12 Hz) and beta (13–30 Hz) oscillatory phase and power at the time of TMS. Phase-dependency of corticospinal excitability was evaluated across a continuous range of power levels using trial-by-trial linear mixed-effects models. For mu, there was no effect of PHASE or POWER ( P > 0.51), but a significant PHASE × POWER interaction ( P = 0.002). The direction of phase-dependency reversed with changing mu power levels: corticospinal output was higher during mu troughs versus peaks when mu power was high while the opposite was true when mu power was low. A similar PHASE × POWER interaction was not present for beta oscillations ( P > 0.11). We conclude that the interaction between sensorimotor oscillatory phase and power gates human corticospinal output to an extent unexplained by sensorimotor oscillatory phase or power alone.